Twining Critical and Creative Approaches to Hypertext Narratives - Salter, Anastasia (Amherst College Press, 2021)
Hypertext is now commonplace: links and linking structure nearly all of our experiences online. Yet the literary, as opposed to commercial, potential of hypertext has receded. One of the few tools still focused on hypertext as a means for digital storytelling is Twine, a platform for building choice-driven stories without relying heavily on code. In Twining, Anastasia Salter and Stuart Moulthrop lead readers on a journey at once technical, critical, contextual, and personal. The book's chapters alternate careful, stepwise discussion of adaptable Twine projects, offer commentary on exemplary Twine works, and discuss Twine's technological and cultural background. Beyond telling the story of Twine and how to make Twine stories, Twining reflects on the ongoing process of making.